FAKTOR-FAKTOR PERTIMBANGAN PEMILIHAN PRODUK MIE INSTAN - Arum Wahyuni Purbohastuti (Tirtayasa Ekonomika, 2018)
The purpose of this research is to know what factors influence buying decision on instant noodle product such as taste, price, brand, easiness to get, portion, availability of flavor variant. Where the samples taken in this study are student KKM Untirta 2016 in the village Padarincang Serang-Banten. This study is a qualitative research by distributing questionnaires of 74 in KKM student in Padarincang. The results obtained are that the factors that most influence the decision in the purchase of instant noodle products is the taste.Keywords : Product, Price, Brand,and buying decision